Outpatient versus inpatient treatment for acute pulmonary embolism - Yoo, Hugo HB [UNESP]; Nunes-Nogueira, Vania Santos [UNESP]; Fortes Villas Boas, Paulo J [UNESP]; Broderick, Cathryn (Wiley, 2019)
Background Pulmonary embolism (PE) is a common life-threatening cardiovascular condition, with an incidence of 23 to 69 new cases per 100,000 people each year. For selected low-risk patients with acute PE, outpatient treatment might provide several advantages over traditional inpatient treatment, such as reduction of hospitalisations, substantial cost savings, and improvements in health-related quality of life. This is an update of the review first published in 2014. Objectives To compare the efficacy and safety of outpatient versus inpatient treatment in low-risk patients with acute PE for the outcomes of all-cause and PE-related mortality; bleeding; adverse events such as haemodynamic instability; recurrence of PE; and patients’ satisfaction. Search methods The Cochrane Vascular Information Specialist searched the Cochrane Vascular Specialised Register, CENTRAL, MEDLINE, Embase, CINAHL and AMED databases, and the World Health Organization International Clinical Trials Registry Platform and ClinicalTrials.gov trials registers, to 26 March 2018. We also undertook reference checking to identify additional studies. Selection criteria We included randomised controlled trials of outpatient versus inpatient treatment of adults (aged 18 years and over) diagnosed with low-risk acute PE. Data collection and analysis Two review authors selected relevant trials, assessed methodological quality, and extracted and analysed data. We calculated effect estimates using risk ratio (RR) with 95% confidence intervals (CIs), or mean differences (MDs) with 95% CIs. We used standardised mean differences (SMDs) to combine trials that measured the same outcome but used different methods. We assessed the quality of the evidence using GRADE criteria. Main results One new study was identified for this 2018 update, bringing the total number of included studies to two and the total number of participants to 451. Both trials discharged patients randomised to the outpatient group within 36 hours of initial triage and both followed participants for 90 days. One study compared the same treatment regimens in both outpatient and inpatient groups, and the other study used different treatment regimes. There was no clear difference in treatment effect for the outcomes of short-term mortality (30 days) (RR 0.33, 95% CI 0.01 to 7.98, P = 0.49; low-quality evidence), long-term mortality (90 days) (RR 0.98, 95% CI 0.06 to 15.58, P = 0.99, low-quality evidence), major bleeding at 14 days (RR 4.91, 95% CI 0.24 to 101.57, P = 0.30; low-quality evidence) and at 90 days (RR 6.88, 95% CI 0.36 to 132.14, P = 0.20; low-quality evidence), minor bleeding (RR 1.08, 95% CI 0.07 to 16.79; P = 0.96, low-quality evidence), recurrent PE within 90 days (RR 2.95, 95% CI 0.12 to 71.85, P = 0.51, low-quality evidence), and participant satisfaction (RR 0.97, 95% CI 0.90 to 1.04, P = 0.39; moderate-quality evidence). We downgraded the quality of the evidence because the CIs were wide and included treatment effects in both directions, the sample sizes and numbers of events were small, and because the effect of missing data and the absence of publication bias could not be verified. PE-related mortality, and adverse effects such as haemodynamic instability and compliance, were not assessed by the included studies. Authors’ conclusions Currently, only low-quality evidence is available from two published randomised controlled trials on outpatient versus inpatient treatment in low-risk patients with acute PE. The studies did not provide evidence of any clear difference between the interventions in overall mortality, bleeding and recurrence of PE.